Analisis Faktor yang Mempengaruhi Permintaan Tenaga Kerja di Indonesia tahun 2015-2023 - Gelin Ramadani; Deden Dinar Iskandar (Universitas Diponegoro, 2024)
This study analyzes the factors influencing labor demand in Indonesia during the 2015-2023 period. The background of this research is based on the importance of inclusive and stable economic growth to improve public welfare by increasing employment opportunities. Labor demand in this study is measured based on several key variables, namely Real Wages, Gross Regional Domestic Product (GRDP), and Investment. The analysis method used is the Panel Data Fixed Effect Model (FEM). This study uses secondary data obtained from the Badan Pusat Statistik and other relevant reports. The results show that, partially, Real Wages and GRDP have a significant effect on Labor Demand, while Investment does not have a partial effect on Labor Demand.